Adjuvant radiation therapy in resected high-grade localized skeletal osteosarcomas treated with neoadjuvant chemotherapy: Long-term outcomes. Issue 1 (April 2016) - Sole, Claudio V.; Calvo, Felipe A.; Alvarez, Eduardo; Cambeiro, Mauricio; Cuervo, Miguel; San Julian, Mikel; Sole, Sebastian; Martinez-Monge, Rafael; Sierrasesumaga, Luis
Abstract: Purpose: To assess long-term outcomes and toxicity of adjuvant radiotherapy in the post-surgical management of patients with resected high-grade skeletal osteosarcomas. Methods and materials: Seventy-two patients with primary resected osteosarcomas underwent adjuvant radiotherapy after neoadjuvant chemotherapy from December 1984 to December 2008. Local control (LC), overall survival (OS) and disease-free survival (DFS) were estimated using Kaplan–Meier methods. For survival outcomes potential associations were assessed in univariate and multivariate analyses using the Cox proportional hazards model. Results: After a median follow-up of 174 months (range, 33–363 months), 10-year LC, DFS, and OS rates were 82%, 58%, and 73%, respectively. In the multivariate analysis only R1 margin status ( p = 0.02) remained significantly associated with LC. Patients with tumor necrosis <90% ( p = 0.04) and R1 resection margin ( p = 0.05) remained at a significantly higher risk of mortality on multivariate analysis. Six patients (8%) developed grade ⩾3 treatment-related chronic toxicity events. No grade 5 toxicities were reported. Conclusions: A multimodal radiotherapy-containing approach is a well-tolerated component of treatment for patients with osteosarcomas undergoing programed resection, allowing low toxicity rates while maintaining high local control rates.